Journal of Umm Al-Qura University for Applied Sciences - Asghar, Basim H.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
Journal of Umm Al-Qura University for Applied Sciences is a peer reviewed (fully) open access journal that publishes original research articles, reviews, reports, short communication as well as case studies. The journal is fully sponsored by Umm Al-Qura University (Saudi Arabia). This means authors can publish free of charge. The journal has a multidisciplinary aspect and it covers: Pure and Applied Mathematics, Statistics and Probability Pure and Applied Physics Chemistry Biology Earth and Environmental Science . .
Keywords: Chemistry; Materials science; Earth sciences; Chemistry; Materials Science; Earth Sciences